FAKTOR DETERMINAN KEJADIAN ANEMIA GIZI BESI PADA IBU HAMIL DI DESA NOELBAKI TAHUN 2010 - Dethan, Maya E.; Jutomo, Lewi; Talahatu, Anna H. (Pergizi Pangan DPD NTT, 2011)
The anemia of iron nutrient is one of the nutrient problems occured in Indonesia and one of main causes of death. The pregnancy have become a vulnerabel group toward iron nutrient anemia as the result of the increase of nutrient needs for mother and fetus. During pregnancy the availabel of iron substance is not comparable with the excalation of blood volume. Manuaba (2007) stated that anemia during pregnancy is strictly dangerous especially when pregnant, giving birth and parturition. The aim of the research is to identify the determinant factors of the incident of iron nutrient anemia toward the pregnancy of Noelbaki in the year of 2010. Variables of the research are iron nutrient anemia, age, age of the pregnancy, the spacing of pregnancy, parity, iron sufficient level of iron substance, prohibited food, and income. Respondents in the research are all pregnancy of Noelbaki that are attempting and following all courses at the local clinic of Noelbaki. The research is analytic research with the design of cross-sectional study. The result of the research base don the multiple logistic regression tests shows that the determinant factor of the incident of iron nutrient anemia of pregnancy in Noelbaki